Swedish crops for the use in production of tempeh : which raw materials grown in the Swedish crop-system can be applied in tempeh production? - Nilsson, Lovisa (SLU/Department of Molecular Sciences, 2020)
With a growing world population, the demands on the food industry are increasing. By reducing the intake of animal protein and replacing it with plant protein, the resource use and emission from the food industry would decrease. Tempeh is a fermented plant food, and acts as a substitute to meats. Tempeh is traditionally made by fermenting soybeans with the mould Rhizopus oligosporus. The objective of the fermentation in the tempeh manufacturing is primarily to alter the sensorial properties of the product and to change the nutritional content, for instance by increasing the bioavailability of nutrients. It is however possible to produce tempeh using other legumes, cereals, oilseeds etc. The aim of the review was to present possible raw materials for tempeh manufacturing that are cultivated in Sweden. The review was limited to include legumes and cereals solely, with the focus were made on aspects like nutritional content, limiting circumstances with the raw material and the impact of tempeh manufacturing has on the mentioned aspects. Four varieties of legumes and four varieties of cereals were included, selected due to their already established production in Sweden, some at larger and some at smaller scales. Limitations with legumes were foremost connected to the content of antinutrients and low yields. The human consumption of legumes in Sweden is limited. Cereals have low protein concentrations and there are already multiple applications of cereals in food products. The quantity of cereals produced in Sweden is much larger than that of legumes and the varieties are more familiar for the consumer. The manufacturing steps decrease the antinutrients content and increase the bioavailability of nutrients in the raw material. The mixture of cereals and legumes in tempeh manufacturing was found to be a possible alternative to get a protein rich product were cereals can tempt the consumer, and the mixture of microorganisms as starter culture was found to have many benefits. Hopefully this review will act as a guideline for the food industry in producing plant-based substitutes to meats where the full potential of the raw material is utilized.